EVALUATION OF ANTI HELICOBACTER PYLORI IGG LEVEL INTHE SERUM OF PATIENTS WITH AUTOIMMUNE THYROIDDISEASE - Aboud, Rana (Iraqi Journal of Science, 2024)
To detect the autoimmune thyroid disease in patients with peptic ulcer caused byH. pylori, we investigated (24) patients with suspected peptic ulcer aged (20 – 35)years old and (10) healthy control. Anti H. pylori IgG were measured in serum ofpeptic ulcer patients by ELISA test. The patients which were positive to anti H.pylori IgG were carried to T3, T4, TSH evaluation by ELISA test. There were ahighly significant differences (P<0.05) inT3,T4 and TSH hormones whencomparison with age groups and gender of patients with peptic ulcer caused by H.pylori and there were a highly significant differences (P<0.05) with increased meanslevel of T3,T4. and TSH hormones in sera of patients afflicted with peptic ulcercaused by H.pylori than control groups.There were a level of anti H. pylori IgG in patients with autoimmune thyroiddisease.